Utilization of Starch Water as Bioethanol using Fermentation Method and Bioactivator with NPK and Urea - Dicky Rinaldi (Eduvest - Journal of Universal Studies, 2021)
Researchers are looking for sustainable alternative fuels that may be utilized as substitutes for petroleum-based materials due to the problem of dwindling petroleum fuels, rising energy demand, and concerns about rising environmental pollution. The solution to this problem is to produce renewable energy. Bioethanol is a product that has a lot of potential in terms of its utility renewable sources of energy In this project, bioethanol will be generated from household waste, namely starch water (rice boiled water), which includes a significant amount of starch and hence has the potential to be used as a raw material for generating bioethanol, as well as reducing household waste, Better still. Fermentation, hydrolysis, neutralization, and distillation are the processes employed in this study. The starch water is used because it has a significant amount of starch (rice cooking water). Because the starch content is not extracted perfectly during the boiling process, it is compared to typical rice washing water. Bioethanol is the end product, and it is intended to be a sustainable energy that will help to solve the energy issue while also reducing and repurposing household trash.